Effect of evolocumab on acute arterial events across all vascular territories : results from the FOURIER trial. (19th September 2021) - Oyama, Kazuma; Giugliano, Robert P; Tang, Minao; Bonaca, Marc P; Saver, Jeffrey L; Murphy, Sabina A; Ruzza, Andrea; Keech, Anthony C; Sever, Peter S; Sabatine, Marc S; Bergmark, Brian A
Abstract: Aims: We assessed the impact of the proprotein convertase subtilisin–kexin type 9 (PCSK9) inhibitor evolocumab on acute arterial events across all vascular territories, including coronary, cerebrovascular, and peripheral vascular beds, in patients with established atherosclerotic cardiovascular disease (ASCVD). Methods and results: In the FOURIER trial, 27 564 patients with stable ASCVD on statin therapy were randomly assigned to evolocumab or placebo. Acute arterial events were a composite of acute coronary (coronary heart disease death, myocardial infarction, or urgent coronary revascularization), cerebrovascular (ischaemic stroke, transient ischaemic attack, or urgent cerebral revascularization), or peripheral vascular (acute limb ischaemia, major amputation, or urgent peripheral revascularization) events. Of the 2210 first acute arterial events, 74% were coronary, 22% were cerebrovascular, and 4% were peripheral vascular. Evolocumab reduced first acute arterial events by 19% (hazard ratio [HR] 0.81 [95% confidence interval 0.74–0.88]; P  < 0.001), with significant individual reductions in acute coronary (HR 0.83 [0.75–0.91]), cerebrovascular (HR 0.77 [0.65–0.92]), and peripheral vascular (HR 0.58 [0.38–0.88]) events. There were 3437 total events (first plus recurrent), with evolocumab reducing total events by 24% (incidence rate ratio 0.76 [0.69–0.85]). The magnitude of reduction in acute arterial events with evolocumab numerically increased over time, with a 16% reduction (HR 0.84 [0.75–0.95]) in the first year followed by a 24% reduction (HR 0.76 [0.67–0.85]) thereafter. Conclusion: The addition of the PCSK9 inhibitor evolocumab to statin therapy reduced acute arterial events across all vascular territories with a robust effect over time, indicating a pan-vascular impact of aggressive lipid-lowering therapy on these acute and clinically meaningful events. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01764633. Graphical Abstract: